2000
DOI: 10.1002/(sici)1096-8628(20000424)91:5<368::aid-ajmg10>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

WHIM syndrome, an autosomal dominant disorder: Clinical, hematological, and molecular studies

Abstract: The acronym WHIM refers to Warts, Hypogammaglobulinemia, Infections, and Myelokathexis. The latter refers to the retention of white cells in the marrow, which becomes hypercellular. We have found approximately 20 examples of WHIM syndrome in the literature under various designations; the first examples are Zuelzer [1964] and Krill et al. [1964]. Chronic noncyclic neutropenia and hypercellular bone marrow represent defective release of marrow cells into the peripheral stream (myelokathexis). The hypermature neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 0 publications
2
59
0
1
Order By: Relevance
“…Interestingly, these genetic studies have also identified phenocopies with the same clinical features but without mutation of CXCR4, suggesting that mutations in as yet uncharacterized downstream regulators of the receptor may be involved in a proportion of cases. and pre-malignant dysplastic changes, necessitating surgical resection of involved tissue [6,10]. Unfortunately for patients with extensive HPV infection, the papillomas are refractory to treatment with standard ablation and immunomodulatory therapies.…”
Section: Viral Susceptibilitymentioning
confidence: 99%
“…Interestingly, these genetic studies have also identified phenocopies with the same clinical features but without mutation of CXCR4, suggesting that mutations in as yet uncharacterized downstream regulators of the receptor may be involved in a proportion of cases. and pre-malignant dysplastic changes, necessitating surgical resection of involved tissue [6,10]. Unfortunately for patients with extensive HPV infection, the papillomas are refractory to treatment with standard ablation and immunomodulatory therapies.…”
Section: Viral Susceptibilitymentioning
confidence: 99%
“…A three-generation pedigree was described with neutropenia, hypogammaglobulinemia, and warts. 265 A mutation in the gene encoding chemokine, CXC motif, receptor-4, CXCR4, is associated with the disease (see Chapter 35). 266 …”
Section: Pearson Syndrome (Omim #557000)mentioning
confidence: 99%
“…First described by Zuelzer in a sporadic case [65], myelokathexis was subsequently found to occur as an autosomal dominant trait in association with hypogammaglobulinemia and dermal/genital papilloma virus infections [66]. Severe infections are rare since neutrophils can be adequately released to the periphery in case of infections.…”
Section: Whim Syndrome (Warts Hypogammaglobulinemia Immunodeficiencmentioning
confidence: 99%